Investigating the effectiveness of the Trigonella foenum-graecum L. (fenugreek) seeds in mild asthma: a randomized controlled trial - Majid Emtiazy; Laleh Oveidzadeh; Minoo Habibi; Leila Molaeipour; Daryush Talei; Zahra jafari; Mahmoud Parvin; Mohammad Kamalinejad (Allergy, Asthma & Clinical Immunology, 2018)
Abstract Background Asthma is one of the important chronic diseases. The asthma prevalence is increasing in last decades. Despite the presence of good controller drugs like corticosteroids, about 60% of asthmatic patients use alternative medicine. This study was done to determine the effectiveness of Tregonella foenum graceum (fenugreek) seeds in mild asthma. Methods It is a double blind trial with placebo effect. One of the ancient prescriptions from Persian Medicine was selected. The participants were divided to three groups randomly. On group received fenugreek syrup one received honey syrup and the third received placebo. Duration of treatment was 4 weeks. Quality of life, Lung function tests and IL-4 levels were evaluated before and after treatment. Results From 90 participants to study 79 completed the process. After study there was significant increase in quality of the life and lung function tests and IL-4 levels in fenugreek and honey groups. Conclusion FEV1 level was improved more than 10% in fenugreek group. Treatment was well tolerated. No serious side effects were reported during the study. The aqueous extract of fenugreek seeds appears to be effective and safe in treatment of mild asthma. Trial registration The study was recorded with the Iranian Registry of Clinical trials [http://www.irci.ir], registration code: IRCT2016011325991N1